Continuous venovenous hemofiltration combined with hemoperfusion for toxic epidermal necrolysis: a retrospective cohort study. (19th May 2017) - Bai, Ming; Yu, Yan; Huang, Chen; Liu, Yirong; Zhou, Meilan; Li, Yangping; Ma, Feng; Jing, Rui; Zhao, Lijuan; Li, Li; Wang, Pengbo; He, Lijie; et al.
Abstract: Aim: The current treatments of toxic epidermal necrolysis (TEN) are limited to the discontinuation of a suspect medication and supportive measures. We conducted a retrospective study to evaluate the efficacy of adding continuous venovenous hemofiltration (CVVH) and hemoperfusion (HP) to the conventional treatment for TEN. Methods: TEN patients who were admitted to our center between January 2008 and May 2016 were considered as candidates. The included patients were divided into the CVVH&HP group ( n = 34) and the conventional group ( n = 34) according to their accepted therapies during hospital stay. Results: The patients in the conventional group had a significantly reduced 28-day survival proportion compared with patients in the CVVH&HP group (73.5 versus 91.2%, p = .047). The adjusted results demonstrated that the conventional group had a significantly higher risk of 28-day mortality as well. Moreover, patients in the CVVH&HP group were associated with significantly shorter hospital stay, rash, fever, and antibiotic durations. However, the addition of CVVH&HP to conventional treatment did not significantly increase the in-hospital cost. Conclusions: In conclusion, CVVH&HP might be a safe and effective adjuvant therapy for TEN. Further well-designed studies are warranted to obtain robust evidence.